Anti-inflammatory effects of triptolide on IgA nephropathy in rats. (3rd September 2015) - He, Liyu; Peng, Xiaofei; Liu, Guoyong; Tang, Chengyuan; Liu, Hong; Liu, Fuyou; Zhou, He; Peng, Youming
Abstract: IgA nephropathy (IgAN) is the finding of immune deposits predominantly containing polymeric IgA in the glomerular mesangium on renal biopsy. Recently studies show that inflammation may involve in the progression of renal glomerulosclerosis and tubulointerstitial scarring in IgAN. This study was designed to evaluate the renoprotective effect of triptolide on IgAN rat model. IgAN was induced in Sprague–Dawley rats by oral and intravenous immunization with BSA for 12 weeks. Rats were treated with triptolide (200 μg/kg/d intragastrically) from 12 to 28 weeks. At Week 28, the rats was sacrificed, kidneys and blood samples were collected for further analysis. Our data shown that IgAN rat model showed marked deterioration of proteinuria together with higher levels of the urine protein:creatinine ratio compared to the normal control. Animals that underwent intermittent exposure to triptolide treatment exhibited significant improvements in the functional parameters without severe side effects. Rats developing IgAN had profound mesangial proliferation and mesangial expansion, intense and diffuse glomerular IgA deposition, while triptolide treatment significantly attenuated it. We also observed that treatment with triptolide significantly decreases serum levels of IL-1β and IL-18, and may exerted anti-inflammatory effects by down-regulating NLRP3 and TLR4 expression. Our study clearly demonstrated that triptolide prevents IgAN progression via an amelioration of inflammasome-mediated proinflammatory cytokine production, thus brought a light of hope for treatment of IgAN.